Marine Invertebrate Larvae Associated with Symbiodinium: A Mutualism from the Start? - Mies, Miguel; Sumida, Paulo Y. G.; Rädecker, Nils; Voolstra, Christian R. (Frontiers in Ecology and Evolution, 2017)
Symbiodinium are dinoflagellate photosynthetic algae that associate with a diverse array of marine invertebrates, and these relationships are comprehensively documented for adult animal hosts. Conversely, comparatively little is known about the associations during larval development of animal hosts, although four different metazoan phyla (Porifera, Cnidaria, Acoelomorpha, and Mollusca) produce larvae associated with Symbiodinium. These phyla represent considerable diversities in larval forms, manner of symbiont acquisition, and requirements on the presence of symbionts for successful metamorphosis. Importantly, the different requirements are conveyed by specific symbiont types that are selected by the host animal larvae. Nevertheless, it remains to be determined whether these associations during larval stages already represent mutualistic interactions, as evident from the relationship of Symbiodinium with their adult animal hosts. For instance, molecular studies suggest that the host larval transcriptome is nearly unaltered after symbiont acquisition. Even so, a symbiosis-specific gene has been identified in Symbiodinium that is expressed in larval host stages, and similar genes are currently being described for host organisms. However, some reports suggest that the metabolic exchange between host larvae and Symbiodinium may not cover the energetic requirements of the host. Here, we review current studies to summarize what is known about the association between metazoan larvae and Symbiodinium. In particular, our aim was to gather in how far the mutualistic relationship present between adult animals hosts and Symbiodinium is already laid out at the time of symbiont acquisition by host larvae. We conclude that the mutualistic relationship between animal hosts and algal symbionts in many cases is not set up during larval development. Furthermore, symbiont identity may influence whether a mutualism can be established during host larval stages.